2021
DOI: 10.3389/fpsyg.2021.716463
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Executive Functions When Reading Multiple Texts: A Systematic Literature Review

Abstract: In the present-day knowledge society, people need to critically comprehend information across multiple sources that express diverse and contradictory viewpoints. Due to the complexity associated with this process, an important role can be played by Executive Functions, that is, cognitive control processes used to regulate mental functioning and behavior when automatized elaborations are not sufficient. The aim of this article is to review existing research on the roles of executive functions when reading from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 86 publications
(169 reference statements)
0
2
0
Order By: Relevance
“…Other systematic reviews go along the same lines, and in the same journal and section Frontiers in Psychology . For example, Dickson and Schubert ( 2020 ) and Liu et al ( 2022 ) found only six studies in a review of great interest; the study by Nguyen et al ( 2021 ) identified 18 eligible articles; Shou et al ( 2022 ) with 12 studies included; or Tarchi et al ( 2021 ); Huang ( 2022 ) found seven studies for quantitative analysis and eight for indirect evidence; Coxen et al ( 2021 ) with 21 articles included in the focal analyzes of the systematic review. The number of studies to be representative is not defined by the number but by the existence of such studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other systematic reviews go along the same lines, and in the same journal and section Frontiers in Psychology . For example, Dickson and Schubert ( 2020 ) and Liu et al ( 2022 ) found only six studies in a review of great interest; the study by Nguyen et al ( 2021 ) identified 18 eligible articles; Shou et al ( 2022 ) with 12 studies included; or Tarchi et al ( 2021 ); Huang ( 2022 ) found seven studies for quantitative analysis and eight for indirect evidence; Coxen et al ( 2021 ) with 21 articles included in the focal analyzes of the systematic review. The number of studies to be representative is not defined by the number but by the existence of such studies.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory control (IC) and working memory have routinely been associated with comprehension ability (Pérez et al, 2014;Tarchi, Ruffini & Pecini, 2021). In a significant study for the present research, Pérez et al (2016) investigated how adults monitor and revise their situation model after encountering unexpected information.…”
Section: High-level Text Comprehension and Inhibitory Controlmentioning
confidence: 98%
“…As an initial step toward synthesizing this literature, we conducted a systematic review of studies reporting concurrent associations among individual differences factors (e.g., working memory) and intertextual integration. Previous efforts to review this literature have revealed many useful insights (Alexander & Disciplined Reading and Learning Research Laboratory, 2020;Anmarkrud et al, 2022;Barzilai & Strømsø, 2018;Bråten et al, 2011;List & Sun, 2023;Richter & Maier, 2017;Tarchi et al, 2021) but are limited by several factors. First, only several reviews have used systematic and transparent search procedures (Anmarkrud et al, 2022;List & Sun, 2023;Richter & Maier, 2017;Tarchi et al, 2021).…”
Section: Individual Differences In Intertextual Integrationmentioning
confidence: 99%
“…Previous efforts to review this literature have revealed many useful insights (Alexander & Disciplined Reading and Learning Research Laboratory, 2020;Anmarkrud et al, 2022;Barzilai & Strømsø, 2018;Bråten et al, 2011;List & Sun, 2023;Richter & Maier, 2017;Tarchi et al, 2021) but are limited by several factors. First, only several reviews have used systematic and transparent search procedures (Anmarkrud et al, 2022;List & Sun, 2023;Richter & Maier, 2017;Tarchi et al, 2021). This is critical for reducing sampling error and for ensuring replicability Cumming et al, 2023).…”
Section: Individual Differences In Intertextual Integrationmentioning
confidence: 99%
See 1 more Smart Citation